IJTIHAD SEBAGAI MODEL PENGEMBANGAN HUKUM ISLAM - Huda, Afiful; Nur Hidayati, Ilma (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2022)
The Qur'an is the first and foremost source of Islamic law. While the Sunnah is the second source of Islamic law. However, Muslims realize that generally the legal provisions contained in the Qur'an and Sunnah are still general in nature and ijmal, do not cover comprehensive and detailed details, so it is felt that ijtihad is very necessary to respond to various problems that arise. The process of developing Islamic law is certainly inseparable from scientific principles, in the sense that Islamic law must be developed scientifically. Therefore, the process of developing Islamic law cannot deny the previous legal thought. The development of Islamic law can be done through several models of ijtihad such as ijthad jama'i and ijtihad fardi, as well as ijtihad intiqa'i and insya'i.